2020
DOI: 10.1016/s2352-3026(20)30143-5
|View full text |Cite|
|
Sign up to set email alerts
|

Implementing newborn screening for sickle cell disease as part of immunisation programmes in Nigeria: a feasibility study

Abstract: Background Sickle cell disease is highly prevalent in sub-Saharan Africa, where it accounts for substantial morbidity and mortality. Newborn screening is paramount for early diagnosis and enrolment of affected children into a comprehensive care programme. Up to now, this strategy has been greatly impaired in resource-poor countries, because screening methods are technologically and financially intensive; affordable, reliable, and accurate methods are needed. We aimed to test the feasibility of implementing a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…HemoTypeSC is affordable, rapid, reliable and accurate diagnostic testing for early infants’ screening programs for SCD in low-resource countries where the prevalence of SCD is high without an organized national newborn screening program [ 19 ]. A similar and larger study in Abuja Nigeria also reported a sensitivity and specificity of 100% with HemoTypeSC and have demonstrated point-of-care tests as reliable and accurate in newborn screening for SCD [ 21 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…HemoTypeSC is affordable, rapid, reliable and accurate diagnostic testing for early infants’ screening programs for SCD in low-resource countries where the prevalence of SCD is high without an organized national newborn screening program [ 19 ]. A similar and larger study in Abuja Nigeria also reported a sensitivity and specificity of 100% with HemoTypeSC and have demonstrated point-of-care tests as reliable and accurate in newborn screening for SCD [ 21 ].…”
Section: Discussionmentioning
confidence: 94%
“…One hundred and eighty-five (74%) of the infants had their haemoglobin genotypes as AA. A similar study in Abuja, Nigeria reported a prevalence of 1·4% for HbSS, 20·5% for HbAS and HbAA 77% [ 21 ]. Another similar study in Awka South-East Nigeria reported a prevalence of 0.3% for HbSS and 75% for HbAA genotype amongst newborns [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point of care testing (POCT) has been recommended as the most cost effective solution for diagnosis of SCD in places with high burden of the disease and limited resources [ 19 , 41 ]. Data from pilot studies on POCT implemented in Africa demonstrated both affordability and reliability of the tests [ 22 , 42 ]. Collectively, these data provide strong evidence on the potential of POCT to be standard practice for SCD diagnosis with the aim of expanding screening coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing screening programs in existing programs and health care infrastructure was recommended by the implementers and policy makers as one of the sustainability strategies. The pilot NBS for SCD that was implemented through the immunization program in Nigeria provided evidence on the feasibility and sustainability of the model in limited resource areas [ 42 ]. Leveraging the limited resources through working with other developed programs in the settings has also been recommended through other experiences [ 4 , 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%